Measurement of drag force on different robots at varying air speeds - Mohammad Firdaus Ahmad
The objective in this project is to study the causes and effect of the drag force on the moving object, to find drag force over bodies like robots at varying air speeds and also for different orientation of robots and to study and familiarize with the wind tunnel.